AMPK is associated with the beneficial effects of antidiabetic agents on cardiovascular diseases. Issue 2 (15th February 2019) - Lu, Qingguo; Li, Xuan; Liu, Jia; Sun, Xiaodong; Rousselle, Thomas; Ren, Di; Tong, Nanwei; Li, Ji
Abstract : Diabetics have higher morbidity and mortality in cardiovascular disease (CVD). A variety of antidiabetic agents are available for clinical choice. Cardiovascular (CV) safety assessment of these agents is crucial in addition to hypoglycemic effect before clinical prescription. Adenosine 5′-monophosphate-activated protein kinase (AMPK) is an important cell energy sensor, which plays an important role in regulating myocardial energy metabolism, reducing ischemia and ischemia/reperfusion (I/R) injury, improving heart failure (HF) and ventricular remodeling, ameliorating vascular endothelial dysfunction, antichronic inflammation, anti-apoptosis, and regulating autophagy. In this review, we summarized the effects of antidiabetic agents to CVD according to basic and clinical research evidence and put emphasis on whether these agents can play roles in CV system through AMPK-dependent signaling pathways. Metformin has displayed definite CV benefits related to AMPK. Sodium-glucose cotransporter 2 inhibitors also demonstrate sufficient clinical evidence for CV protection, but the mechanisms need further exploration. Glucagon-likepeptide1 analogs, dipeptidyl peptidase-4 inhibitors, α-glucosidase inhibitors and thiazolidinediones also show some AMPK-dependent CV benefits. Sulfonylureas and meglitinides may be unfavorable to CV system. AMPK is becoming a promising target for the treatment of diabetes, metabolic syndrome and CVD. But there are still some questions to be answered.